68.3k views
1 vote
(y+6) (y+13) find the product
step by step explanation pls​

User Wardw
by
6.0k points

2 Answers

5 votes
(y+6) (y+13)
Multiply 1st y by 2nd y = y^2
Multiply 1st y by +13 = +13y
Multiply +6 by 2nd y = +6y
Multiply +6 by +13 = +78

[y^2 + 13y + 6y + (6x13)]

y^2 + 19y + 78

:. (y+6) (y+13) = y^2 + 19y + 78
User JLo
by
4.7k points
3 votes

Answer:

(y + 6)(y + 13) = y² + 19y + 78

Explanation:


\rm \implies (y + 6)(y + 13) \\ \\ \rm \implies y(y + 13) + 6(y + 13) \\ \\ \rm \implies {y}^(2) + 13y + 6y + 78 \\ \\ \rm \implies {y}^(2) + 19y + 78

User Haccks
by
4.8k points